Factors affecting the adoption and use of online assessment for learning at Polytechnics in Zimbabwe - Gilbert Mahlangu; Lucia Makwasha (Taylor and Francis Group, 2023)
The purpose of this study was to investigate the key factors affecting the adoption and use of online assessment in Polytechnics in Zimbabwe during the COVID-19 era using the Technology-Organisation-Environment (TOE) framework and Technology Acceptance model (TAM). A qualitative research methodology was employed to discover and explain the adoption factors of online assessment for learning based on the participants’ experiences. Data were collected from lecturers and students from Harare Polytechnic using semi-structured interviews. Total of 10 students and five lecturers were purposively selected from five Departments. The factors affecting the adoption and use of online assessment were coded using Template analysis and classified based on the theoretical lens of the integration of the TOE framework and TAM. The study reveals that the adoption and use of online assessment in Polytechnics depend on technological factors (internet access, computing devices, and ICT infrastructure), organisational factors (institutional support), environmental factors (academic integrity), and individual factors (digital skills and user perceptions). This study concludes that online assessment is no longer a choice for tertiary education institutions since COVID-19 has presented a mandatory environment for its adoption. As far as theoretical contributions of this study are concerned, the study extends the TOE framework by explaining how the individual factors, for instance, the digital skills and user perceptions influence the successful adoption of technology in mandatory environments such as online assessment during COVID-19. In terms of practical contributions, the extended TOE framework can be used as a valuable point of reference for scaling up the adoption and use of online assessment in Polytechnics. The study recommends that both lecturers and students should be trained on the usage of an online assessment.